Impact of El Niño–Southern Oscillation (ENSO) and Rainfall Variability on Rice Production in East Java during 2018–2025 - Canggih Nailil Maghfiroh; Amalia Malik; Helda Jaya Puspita; Rallyanta Tarigan; Rini Hardiyani (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
El Niño –Southern Oscillation (ENSO) is one of the climate variability factors that can affect rainfall patterns and agricultural production systems . This study aimed to analyze the relationship between ENSO variability , rainfall , harvested area, and rice production in East Java during 2018–2025. The research used a quantitative descriptive method with secondary data obtained from the Meteorology , Climatology , and Geophysical Agency and the Central Bureau of Statistics . Data analysis was performed using Pearson correlation analysis to determine the relationship among variables . The results showed that ENSO had a very strong negative correlation with rainfall (r = -0.959; p < 0.01), indicating that stronger El Niño conditions were associated with lower rainfall . However , ENSO and rainfall did not show a significant direct relationship with rice production . Rice production showed a very strong positive correlation with harvested area (r = 0.979; p < 0.01), indicating that harvested area was the main factor associated with production changes during the observation period . These findings indicate that although ENSO strongly influences rainfall variability , its impact on rice production can be reduced by agricultural management factors such as irrigation systems , cultivation practices , adaptive varieties , and farmer adaptation strategies .